Sierra Leone : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Financing Assurances Review, and Request for Waivers of Nonobservance of Performance Criterion, Extension of the Arrangement, and Rephasing of Disbursements-Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report, 2008)
This paper discusses key findings of the Second Review Under the Poverty Reduction and Growth Facility (PRGF) program for Sierra Leone. Performance under the IMF-supported program was mixed. Output growth was strong at 6.8 percent and broad-based, but key fiscal revenue and spending objectives were missed, and progress on the structural reform front was slow. The authorities' program for 2008 aims to mobilize more domestic revenue; reorient public spending to infrastructure projects and poverty-reducing programs; prevent rapid accumulation of public debt; and accelerate implementation of structural reforms.